Analysis of health seeking behavior of farming families in Kayu Aro, Kerinci - Azhary, Muhammad Rifqi; Hidayat, Ahmad Thohir; Wulansari, Arnati; Ningsih, Vinna Rahayu (Proceedings Academic Universitas Jambi, 2025)
Background: Kayu Aro District in Kerinci Regency, Jambi Province, is a mountainous agricultural area with unique geographic and socio-cultural characteristics. The majority of its population is farmers, primarily tea and vegetable growers. Based on data from the Kayu Aro Community Health Center (Puskesmas) in 2023, local residents tend to delay seeking formal treatment when experiencing health problems, primarily due to limited access to health facilities, the availability of traditional medicine, and economic factors. The geographical location, which includes highlands with limited transportation access, contributes to the unique patterns of healthcare seeking in this region. Objective: The objective of this study is to analyze the family medicine seeking behavior of farmers in Kayu Aro and to analyze community beliefs about the treatment of family diseases. Methods: This study uses a qualitative research method by interviewing 5 informants and using thematic analysis. Results: This study describes several common illnesses experienced by families, including fever, influenza, gout, ulcers, pruritus, back pain, hypotension, and others. Furthermore, people still rely on traditional healing methods before seeking medical care. Conclusion: Families still use traditional methods to treat family illnesses, especially when in the garden, because the distance to health facilities is too far.